Gender, Race, and Policy: Aboriginal Women and the State in Canada and Australia - McGrath, Ann; Stevenson, Winona (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1996)
This article examines the history of colonial and national policies towards indigenous peoples in Australia and Canada during the 19th and 20th centuries. It is specifically concerned with the ways in which such legislation affected Aboriginal women. In attempting to provide a comparative assessment of the "statutory subjugation" of Aboriginal women, the article examines the law's definition of identity and band membership; enfranchisement and assimilation; personal autonomy (marriage, divorce, sexuality, motherhood); private and personal property; and political reorganization. It concludes that gender and race were key determinants of government policy in both countries, and that under the Canadian Indian Act and Australian Aboriginal Acts, women, in particular, suffered a great decline in status and severe limitations of autonomy. But the failure of state policies to bring about the complete degradation of Aboriginal women in particular, and Aboriginal peoples in general, suggests that there were forces operating to "destabilize ... hegemonic colonial control." Competing colonial values, collective resistance of Aboriginal societies, and the individual contestations of both colonizer and colonized, in the end, undermined imperial objectives.